2012
DOI: 10.1016/j.apt.2011.11.004
|View full text |Cite
|
Sign up to set email alerts
|

Preparation of nanostructured nickel aluminate spinel powder from spent NiO/Al2O3 catalyst by mechano-chemical synthesis

Abstract: a b s t r a c tIn this paper, the possibility of mechano-chemical synthesis, as a single step process for preparation of nanostructured nickel aluminate spinel powder from NiO/Al 2 O 3 spent catalyst was investigated. Powder samples were characterized in terms of composition, morphology, structure, particle size and surface area using complementary techniques such as X-ray diffraction (XRD), scanning electron microscopy (SEM), transmission electron microscopy (TEM), differential thermal analysis (DTA) and volu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
24
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(30 citation statements)
references
References 19 publications
2
24
0
1
Order By: Relevance
“…The strong sharp diffraction peaks indicate that NiAl 2 O 4 calcined at 1200 ℃ has a long-range ordered structure. These results correlate well with the previous study by Nazemi et al [19] who www.springer.com/journal/40145 found that a mixture of NiO and Al 2 O 3 powders transformed to the single phase NiAl 2 O 4 spinel powders after calcination above 1000 ℃, at 1100 ℃ for 15 h milled powders, and at 1400 ℃ for unmilled powders. For the CuAl 2 O 4 samples ( Fig.…”
Section: Xrd Analysissupporting
confidence: 92%
See 1 more Smart Citation
“…The strong sharp diffraction peaks indicate that NiAl 2 O 4 calcined at 1200 ℃ has a long-range ordered structure. These results correlate well with the previous study by Nazemi et al [19] who www.springer.com/journal/40145 found that a mixture of NiO and Al 2 O 3 powders transformed to the single phase NiAl 2 O 4 spinel powders after calcination above 1000 ℃, at 1100 ℃ for 15 h milled powders, and at 1400 ℃ for unmilled powders. For the CuAl 2 O 4 samples ( Fig.…”
Section: Xrd Analysissupporting
confidence: 92%
“…CuAl 2 O 4 and CuO were observed as intermediate phases at 900 and 1000 ℃ before transforming to CuAlO 2 final phase at 1100 ℃. Nazemi et al [19] investigated the effect of calcination temperature on NiAl 2 O 4 powders synthesized by mechano-chemical process. The single phase NiAl 2 O 4 spinel powders were obtained at 1400 (unmilled powders) and 1100 ˚C (15 h milled powders) ; however, their optical properties have not been examined.…”
Section: Introductionmentioning
confidence: 99%
“…However, Figure 3 shows that the presence of nickel aluminate NiAl 2 O 4 cannot be ruled out since its XRD lines overlap with the lines characteristic of transition alumina. 38 After TPR, Ni 0 diffraction lines are clearly present at 2θ = 52 and 76°. Therefore, although the reduction process of the catalyst supported on alumina requires higher temperature under TPR conditions than the reduction of the catalyst supported on silica, the reduction mainly transforms NiO to metallic nickel in both cases.…”
Section: Resultsmentioning
confidence: 97%
“…In addition, both samples present high surface area, with strong reduction of surface area for the heated sample at 800 o C (126 m 2 /g) in comparison with the heated sample at 700 o C (154m 2 /g), indicating that the increase of heating temperature causes a decrease of them. For purposes of comparison, some values of surface area can be found in literature for NiAl 2 O 4 powders synthesized by other methods, such as 22-35 m 2 /g (combustion reaction using glycine as fuel) [23], 42.3 m 2 /g (mechanochemical synthesis) [20], 107 m 2 /g (microwave combustion) [35], 108 m 2 /g (sonochemical) [17], 58-119 m 2 /g (sol-gel using gelatin as organic precursor) [37], 138 m 2 /g (sol-gel using propionic acid as solvent) [4], 186 m 2 /g (combustion reaction using urea as fuel) [22], and 200-300 m 2 /g (sol-gel using metal alkoxide precursors) [12]. Despite sol-gel method using metal alkoxide precursors [12] and combustion route using urea as fuel [22] generate powders with higher surface area, the method proposed in this workalso resulted intoa material containing a high surface area, comparable and superior than the ones obtained by other routes.…”
Section: Resultsmentioning
confidence: 99%
“…Due to its high mechanical resistance, as well as its high thermal and chemical stabilities, nickel aluminate has been employed as catalyst support in various chemical reactions such as 1, 2, 4-trichlorobenzene hydrodechlorination [2], partial oxidation of methane to syngas [3], CO 2 reforming of methane [4], chemical-looping combustion [5,6], acetylene hydrogenation [7], steam reforming of methane [8,9], combustion of methane [10] and steam reforming of glycerol to hydrogen production [11]. NiAl 2 O 4 particles have been prepared by various routes such as sol-gel [12,13], solid state reaction [14], microwave [15,16], sonochemical [17], Pechini method [18], thermal decomposition of polynuclear malate complexes [19], mechano-chemical synthesis [20], one-pot process [21] and combustion route [22][23][24]. In this work, we proposethe use of an alternative route for the preparation of NiAl 2 O 4 spinel.…”
Section: Introductionmentioning
confidence: 99%